2021
DOI: 10.1038/s41598-021-83330-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of involved margins in breast specimens with X-ray phase-contrast computed tomography

Abstract: Margins of wide local excisions in breast conserving surgery are tested through histology, which can delay results by days and lead to second operations. Detection of margin involvement intraoperatively would allow the removal of additional tissue during the same intervention. X-ray phase contrast imaging (XPCI) provides soft tissue sensitivity superior to conventional X-rays: we propose its use to detect margin involvement intraoperatively. We have developed a system that can perform phase-based computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Conventional techniques such as optical microscopy or spectroscopy provide volumetric information but have, in general, a reduced penetration depth, hindering their application to large specimens such as large wide local excisions or mastectomies [4], [5]. On the other hand, while X-rays are one of the methods of choice for breast cancer screening, their application to intra and post-operative assessment of breast specimens is still the subject of investigations [6], [7]. The main limitation is that, while conventional Xray imaging provides sufficient penetration depth and good spatial resolution, it provides limited soft tissue contrast if staining agents are not used, which affects its application to biomedical imaging.…”
Section: Index Terms-breast Conserving Surgery Multiresolution Imagin...mentioning
confidence: 99%
“…Conventional techniques such as optical microscopy or spectroscopy provide volumetric information but have, in general, a reduced penetration depth, hindering their application to large specimens such as large wide local excisions or mastectomies [4], [5]. On the other hand, while X-rays are one of the methods of choice for breast cancer screening, their application to intra and post-operative assessment of breast specimens is still the subject of investigations [6], [7]. The main limitation is that, while conventional Xray imaging provides sufficient penetration depth and good spatial resolution, it provides limited soft tissue contrast if staining agents are not used, which affects its application to biomedical imaging.…”
Section: Index Terms-breast Conserving Surgery Multiresolution Imagin...mentioning
confidence: 99%
“…When a sample is placed in the beam, the X-rays change their direction of propagation due to refraction [26]. The used system [27] included a Rigaku MicroMax 007 HF rotating anode molybdenum source with a 70 µm focal spot, operating at 40 kVp and 20 mA. The detector was an indirect flat panel CMOS detector with a 50 x 50 µm 2 pixel size.…”
Section: Porosity (%)mentioning
confidence: 99%
“…Experimental studies have demonstrated the ability of x-ray phase contrast imaging to yield a higher contrast-to-noise ratio (CNR) than conventional attenuation-based x-ray imaging. In particular, this applies to samples with weak intrinsic x-ray attenuation such as soft biological tissue [13][14][15][16] , a category that includes surgically excised human tissue, which explains why the technology is receiving attention in the context of intraoperative specimen imaging [3][4][5]17 .…”
Section: Edge-illumination X-ray Phase Contrast Imagingmentioning
confidence: 99%
“…Our group has developed dedicated x-ray phase contrast micro-computed tomography (CT) scanners for the intraoperative margin assessment of resected tumours [3][4][5] . These implement "edge-illumination" (EI), utilising masks to generate separated x-ray beamlets and analyse their refraction.…”
Section: Introductionmentioning
confidence: 99%